'Under pressure': is there a link between orthostatic hypotension and cognitive impairment in α-synucleinopathies?. Issue 12 (9th September 2016) - Udow, Sean J; Robertson, Andrew D; MacIntosh, Bradley J; Espay, Alberto J; Rowe, James B; Lang, Anthony E; Masellis, Mario
Abstract : Parkinson's disease, dementia with Lewy bodies and multiple system atrophy are characterised by abnormal neuroglial α-synuclein accumulation. These α-synucleinopathies have in common parkinsonism and non-motor features including orthostatic hypotension (OH) and cognitive impairment. However, the nature of the relationship between OH and cognitive impairment is unclear. We therefore systematically reviewed the literature for evidence of an association between OH and cognitive impairment in α-synucleinopathies and discuss possible mechanisms and implications of this relationship. Abstracts from 313 original research articles were surveyed, and a total of 132 articles were considered for this review. Articles were stratified as: 'direct-evidence studies' based on the direct assessment for a relationship between OH and cognitive impairment in α-synucleinopathies, and 'indirect-evidence studies' based on an association being referred to as a secondary outcome. Ten 'direct-evidence papers' were identified, seven of which reported a positive association between OH and cognitive impairment, while seven of 12 'indirect-evidence papers' similarly did as well. The papers that reported no association between OH and cognitive impairment used less sensitive measures of cognition. A relationship between OH and cognitive impairment in patients with α-synucleinopathies exists, but the underlying mechanisms remain unclear. Three hypotheses are proposed: (1) OH and cognitive impairment occur concurrently due to diffuse brain and peripheral deposition of α-synuclein, (2) OH-mediated cerebral hypoperfusion impairs cognition and (3) the two act synergistically to accelerate cognitive decline. Longitudinal neuroimaging studies and clinical trials may help clarify the nature of this relationship.